Effect of Various Finishing and Polishing Systems on Surface Roughness of Nanohybrid and Microhybrid Composites - farahat, farnaz; davari, abdolrahim; Hakimzade ardakani, Alireza; moslehi, marzie (Journal of Dental School, 2020)
Objectives Finishing and polishing systems may affect the surface properties of composite resins. In this in vitro study, we evaluated the surface roughness of two composite resins after polishing with three different polishing systems. Methods Thirty-six specimens (8 mm diameter × 2 mm thickness) were fabricated from Kalore nanohybrid and Gradia Direct microhybrid composite in a Teflon mold and divided into four groups according to the polishing protocol (n=9): control group, Sof-Lex, Super Snap, and Jiffy. The mean surface roughness (Ra) values were determined using a profilometer and the surface of two samples in each group was observed under a scanning electron microscope (SEM). Data were analyzed using one-way and two-way ANOVA. The significance level was set at 5%. Results Profilometric evaluation showed that in both composite resins, the smoothest surfaces were obtained with Mylar strip; also Jiffy showed significantly higher Ra values than other polishing systems. Type of composite and polishing technique had significant effects on surface roughness (P=0.0001). SEM observations also showed that surface roughness of Jiffy was more than that of three other groups. Conclusion After the use of finishing and polishing systems, the surface roughness of Gradia was higher than Kalore in all polishing systems. Sof-Lex and Super Snap were effective on Gradia, and jiffy created the roughest surface.